Bioinspired Color Change through Guided Reflection. Issue 24 (21st October 2018) - He, Jiaqing; Song, Chengyi; Shan, Hao; Jiang, Yiyue; Zhou, Lingye; Tao, Peng; Wu, Jianbo; Shang, Wen; Deng, Tao
Abstract: Color change to match background has attracted particular attentions for many civil and military applications. Different from most current efforts in adaptive color change that include active color processing and generation, in this work a new passive color‐change approach without the need of color processing and generation is proposed. Such approach takes inspiration from the biological camouflage systems such as those in the midwater squid Galiteuthis, which use "leaky" fiber‐like cells to guide lights around their eyes for effective camouflage from their upward‐looking predators. In the approach, the bioinspired color‐change system directly takes the reflected light from the background, guides and displays it around the surface of the target. This bioinspired color‐change approach is dependent on a waveguide‐based system that includes light receiving, transporting, and display modules. Through the improvement of the efficiency in light collection, guiding, and display, both the experimental studies and computational modeling demonstrate the performance of such approach in the entire visible region with both spectra matching and rapid dynamic response. Through the design of pixelated modules, this new approach also shows good color matching with patterned color background and provides a feasible route to camouflage in a complex natural background. Abstract : Inspired by the biological camouflage systems in the midwater squid Galiteuthis, a new color‐change approach using guided reflection is proposed and demonstrated. By directly coupling the background reflection and displaying the reflected light on the surfaces of target, the bioinspired color‐change approach achieves both the faithful spectra matching with background and rapid dynamic response in the entire visible region.